Robots and Immigrants: Employment, Precarisation and the Art of Neoliberal Governance - Kostas Maronitis (Angles)
This article identifies the points of divergence and convergence between the discourses of technological displacement and low-skilled immigrant labour and argues for the understanding of a new model of neoliberal governance. New technologies, new managerial and organisational strategies, and new models of exploitation emerged in the aftermath of the 2008 financial crisis in the UK. What are the main features of this crisis? The article points to two different yet interconnected processes. First, due to demands for higher productivity and economic growth the advent of automation, robotics and AI is presented as an irreversible process capable of producing a new corporate environment in which low labour costs and efficiency co-exist with massive job losses, waning of workers’ collective defences and re-training programmes. Second, for all the increasing popularity of protectionist politics and of demands for tight immigration controls the need for low paid and low-skilled immigrant labour across several sectors of the UK economy remains unchanged. Demands for economic growth render the presence of low-skilled immigrants necessary as long as they are subjected to the minimum political, economic and social provisions such as wages, political participation and mobility. As a result, low-skilled immigrants must exist within a political and economic environment in which they are perceived as useful and at times essential accessories for sustaining economic growth and public services. The concepts of precarisation and precarity provide a useful insight into the underlying logic that connects and differentiates those two discourses. In particular, precarisation becomes at once the dominant mode of governing the population and the most effective means for capital accumulation. In contradistinction to old understandings of government that demanded political compliance in exchange for the promise of social protection, the neoliberal process of precarisation increases instability and provides the minimum of insurance. Precarisation is not limited to employment but more generally to the formulation of homo œconomicus as a collective neoliberal subject living in fear and uncertainty. Precarity, on the other hand, designates a sense of hierarchy amongst insecure workforce and the compensations they receive. The article concludes by arguing that the dividing lines between national and foreigner, domestic and immigrant, become integral notions of neoliberal governance for differentiating between precarious groups and maintaining order in contemporary capitalism.